“My Parent is so Stubborn!”—Perceptions of Aging Parents’ Persistence, Insistence, and Resistance - Heid, Allison R. (J Gerontol B Psychol Sci Soc Sci, 2016)
OBJECTIVE: Aging parents may respond to advice or help with daily problems from their grown children by insisting, resisting, or persisting in their ways or opinions, behaviors which are commonly viewed as stubbornness. Research has not examined how frequently such behaviors occur and what factors are associated with these behaviors. METHODS: Middle-aged adults and parents (N = 189 dyads) reported the prevalence of parental behaviors attributed to stubbornness. Utilizing hierarchical linear regression and multilevel modeling this exploratory study examined the association of parent stubbornness with individual and relationship-based characteristics and concordance in reports within dyads. RESULTS: Over 77% of children and 66% of parents reported parents acting in ways attributed to stubbornness at least sometimes. Children reported higher levels of parental stubbornness than parents self-reported. Children’s perceptions of occurrence were related to parent disability and relationship characteristics, while parents’ self-reports were associated with their own personalities. Discrepancies in reports between parents and children were associated with child and parent characteristics. DISCUSSION: This novel exploration demonstrated that individual and relationship-based factors are linked to the perceived expression of stubbornness by parents and that there is discordance in perceptions within families. Findings suggest a need for intervention to increase understanding within families.